2023
DOI: 10.3389/fsufs.2023.1127164
|View full text |Cite
|
Sign up to set email alerts
|

Halal or not? Exploring Muslim perceptions of cultured meat in Singapore

Abstract: Singapore was the first country to approve cultured meat for public consumption. However, it remains unclear whether Muslims, who adhere to religious dietary restrictions and constitute a significant proportion of Singapore's population, are willing to consume cultured meat. Informed by the cognitive miser model, this study explores how Muslims make sense of cultured meat through their religious beliefs, trust in different stakeholders, as well as their risk or benefit perceptions of cultured meat. The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The intention to consume, as captured in our study, reflects individuals future behavior, with the assumption that cultured meats will eventually attain halal certification in the future. Focus group discussions with Singaporean Muslims revealed that Muslims are unwilling to try cultured meat without halal certification (Ho et al, 2023). Hence, it is important to emphasize that our finding is contingent upon the future halal status of cultured meat.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…The intention to consume, as captured in our study, reflects individuals future behavior, with the assumption that cultured meats will eventually attain halal certification in the future. Focus group discussions with Singaporean Muslims revealed that Muslims are unwilling to try cultured meat without halal certification (Ho et al, 2023). Hence, it is important to emphasize that our finding is contingent upon the future halal status of cultured meat.…”
Section: Discussionmentioning
confidence: 80%
“…Other studies (e.g., Usman et al, 2021) found that halal-conscious Muslims are more discerning and take a more active stance in selecting and seeking information on the products that they consume and are more likely to proactively seek and pay attention to existing coverage of cultured meat in local media. In the context of cultured meat in Singapore, previous focus group discussions found that Singaporean Muslims are generally aware of the potential environmental and food security benefits of cultured meat (Ho et al, 2023), in line with the media coverage of cultured meat in Singapore's local newspaper. Therefore, we propose that:…”
Section: Halal Consciousnessmentioning
confidence: 86%
See 3 more Smart Citations